Coworker Networks in the Labour Market - Albrecht Glitz (Institute for the Study of Labor (IZA), 2013)
This paper studies the effect of coworker-based networks on individual labour market outcomes. I analyse how the provision of labour market relevant information by former coworkers affects the employment probabilities and, if hired, the wages of male workers who have previously become unemployed as the result of an establishment closure. To identify the causal effect of an individual worker's network on labour market outcomes, I exploit exogenous variation in the strength of these networks that is due to the occurrence of mass-layoffs in the establishments of former coworkers. The empirical analysis is based on administrative data that comprise the universe of workers employed in Germany between 1980 and 2001. The results suggest a strong positive effect of a higher employment rate in a worker's network of former coworkers on his re-employment probability after displacement: a 10 percentage point increase in the prevailing employment rate in the network increases the re-employment probability by 7.5 percentage points. In contrast, there is no evidence of a statistically significant effect on wages.
Keywords: J63; J64; 330; networks; labour markets; employment; wages